Comparative Evaluation of Surface Roughness of Resin- Modified Glass Ionomer and Glass Hybrid Restorative Materials Simulated by Tooth Brushing: An in-Vitro Study - Divya Rao Komandla; Shashi Rashmi Acharya; Kalyana Chakravarthy Pentapati (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare the effect of tooth brushing on surface roughness of Resin-Modified Glass Ionomer Cement (RMGIC; GC Gold label 2LC Light Cured Universal Restorative) and Glass Hybrid (GH; GC EQUIA SYSTEM- EQUIA Forte™ Fil and EQUIA Forte™ Coat) restorative material at 1- and 3-months interval simulated by tooth brushing. Material and Methods: RMGIC and GH material specimens (20 each) were prepared according to manufacturer instructions in 10 mm × 2 mm dimensions using a mylar strip. A specially designed toothbrush simulator was used along with Oral B Pro 2 2000N powered toothbrush and Colgate Total dentifrice (Colgate-Palmolive India limited; Relative dentin abrasivity - RDA: 70 - Low abrasive) to perform brushing strokes. Specimens were subjected to surface roughness analysis before and after simulated tooth brushing at baseline, 1, and 3 months. Results: The intragroup comparison was done using repeated-measures ANOVA. Intergroup comparisons were done using an independent sample t-test and General Linear Model (ANCOVA). Surface roughness increased from baseline through 3 months in both RMGIC and GH groups. The mean surface roughness in RMGIC group was significantly higher than GH group at baseline 1 and 3-months, respectively (p<0.001, <0.001, and <0.001). Interaction between group and baseline surface roughness was not significant (p=0.466).  The estimated marginal means were significantly higher in RMGIC than GH group (p=0.008). Conclusion: The surface roughness of both RMGIC and GH restorative increased from baseline to 1 month and 3 months after the simulated toothbrushing protocol. GH exhibited significantly lower surface roughness than RMGIC at all the tested intervals.